Three siblings with Prader–Willi syndrome caused by imprinting center microdeletions and review. Issue 4 (13th February 2018) - Hartin, Samantha N.; Hossain, Waheeda A.; Weisensel, Nicolette; Butler, Merlin G.
Abstract : Prader–Willi syndrome (PWS) is a complex genetic imprinting disorder characterized by childhood obesity, short stature, hypogonadism/hypogenitalism, hypotonia, cognitive impairment, and behavioral problems. Usually PWS occurs sporadically due to the loss of paternally expressed genes on chromosome 15 with the majority of individuals having the 15q11‐q13 region deleted. Examples of familial PWS have been reported but rarely. To date 13 families have been reported with more than one child with PWS and without a 15q11‐q13 deletion secondary to a chromosome 15 translocation, inversion, or uniparental maternal disomy 15. Ten of those 13 families were shown to carry microdeletions in the PWS imprinting center. The microdeletions were found to be of paternal origin in nine of the ten cases in which family studies were carried out. Using a variety of techniques, the microdeletions were identified in regions within the complex SNRPN gene locus encompassing the PWS imprinting center. Here, we report the clinical and genetic findings in three adult siblings with PWS caused by a microdeletion in the chromosome 15 imprinting center inherited from an unaffected father that controls the activity of genes in the 15q11‐q13 region and summarize the 13 reported cases in the literature.